Covid impacts on banana producing countries – survey June 2020 - Chase, Rachel; Dita Rodriguez, Miguel; Ekesa, B.; Zheng, Sijun; Roux, Nicolas Stephan M. (2021)
We carried out a survey to determine the impacts of Covid 19 on the banana industry in banana producing countries through our regional networks